RESPON DUA VARIETAS BAWANG MERAH (Allium ascalonicum L.) DALAM MENINGKATKAN PRODUKSI DENGAN PEMBERIAN PUPUK KCL DI KECAMATAN RANTAU SELATAN - Fitra Syawal Harahap; Hilwa Walida (UNIVERSITAS LABUHANBATU, 2020)
The decline in productivity of shallots (Allium ascalonicum L.) is one of the horticultural crops that are consumed by many Indonesian people, therefore it is necessary to provide potassium elements on the onion crop. Where potassium in plants is very important, it plays a role as a factor in the enzymes in the process of plant metabolism, stomata regulation, and CO assimilation. Meanwhile, if the lack of potassium causes small tubers so that production decreases. This study aims to determine the response of growth and yield of onion (Allium ascalonicum L.) to several varieties and dosages of KCL fertilizer. This research was conducted in the experimental area of the Faculty of Science and Technology of Labuhabatu University, South Rantau District with a height of 13 meters above sea level. The materials used in this study were Sumenep and Maja Cipanas Shallot Seed Varieties, Urea Fertilizer, TSP and KCl. The tools used in this study are the Global Positioning System (GPS), hoe, fat, meter, sample traces, scales, ovens and stationery that support this research. This research uses factorial randomized block design with 2 factors and 3 replications, namely: Factor 1: V1 = Variety of Sumenep and V2 = Maja Cipanas and Factor 2 of fertilizer dose P0 ,, Control, P1 = 50 gram / plot, P2 = 100 gram / plot, P3 = 150 gram / plot). The parameters observed were sample wet weight, plot dry weight, and the number of plot production. Research Results Showing the dosage treatment gave an effect on the growth and production of shallots with the best dose of 150 grams/plot. An interaction occurred between KCL fertilizer dosage and onion varieties on plant height, number of leaves, number of tubers, wet weight, number of production and dry weight of onion plants. Keywords: Shallot, KCL Fertilizer, Production Results, Rantau Selatan District